Modeling the enablers of blockchain technology implementation for information management in healthcare supply chains - Matthew Quayson; Eric Kofi Avornu; Albert Kweku Bediako (Modern Supply Chain Research and Applications, 2024)
Purpose - Blockchain technology enhances information management in healthcare supply chains by securing healthcare information and providing medical resource traceability. However, there is no decision framework to support blockchain implementation for managing information, especially in emerging economies' healthcare supply chains. This paper develops a hierarchical decision model for implementing blockchain technology for information management in emerging economies' healthcare supply chains. Design/methodology/approach - This study uses 20 health supply chain experts in Ghana to rank 17 decision criteria for implementing blockchain for healthcare information management using the best-worst method (BWM) multi-criteria decision technique. Findings - The results show that "security" and "privacy," "infrastructural facility" and "presence of training facilities" are the top three critical factors impacting blockchain adoption in the health supply chain for healthcare information management. Other sub-factors are prioritized. Practical implications - To implement blockchain effectively to enhance information management in the healthcare supply chain, health institutions, blockchain technology providers and state authorities should concentrate on the highly critical factors extracted from the study. Originality/value - This is the first study that develops a hierarchical decision model for implementing blockchain technology in emerging economies' health supply chains.
Keywords: 650; Healthcare information management; TOE; Blockchain technology; Best-worst method; Emerging economies